Paradigma Pembelajaran Bahasa Arab (Analisis Kontrastif Metode Pembelajaran Konvensional dan Kontemporer) - Haq, Muhammad A'inul; Mulyani, Slamet; Sholeh, Ahmad (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2023)
This study uses the interpretivism paradigm to analyze the contrast between conventional and contemporary teaching methods in learning the Arabic language. The conventional teaching method emphasizes mastery of grammar and vocabulary through structured methods, while the contemporary method prioritizes communication and understanding of Arab culture. A literature review was conducted to understand the perspectives of experts in Arabic language learning and shows that contemporary teaching methods are more suitable for Arabic language teaching because it emphasizes communication skills and understanding of Arab culture. However, some studies show that conventional teaching methods are still crucial in strengthening the structured mastery of grammar and vocabulary. This article recommends using contemporary teaching methods in Arabic language learning by paying attention to the structured mastery of grammar and vocabulary and developing appropriate learning strategies based on students' needs and contextual factors.